Performance improvement in Yo-Yo intermittent recovery test level 2 and during official matches: The role of speed endurance training production in elite football players - Izzo, R.; Altavilla, G.; Cejudo, A.; Raiola, G.; D`Isanto, T.; Giovannelli, M. (SportMont, 2020)
This study aims to examine the performance improvement in yo-yo intermittent recovery test level 2 (IR2) and official matches, during a competitive season in professional football players (Italian 3rd Division Series C, 2019- 2020). Twenty-eight (n=28) élite football players participated in this study (age 21.4±3.3; body weight 79.7±3.4; height 182.4±5.5; fat mass 9.2±1.9), without goalkeepers. In the pre-season (4 weeks, from July to August), the players performed yo-yo intermittent recovery test level 2 (IR2), to evaluate aerobic and anaerobic performance before the start of the season. Every player has been analysed with a K-GPS Live device 50Hz (K-Sport Universal STATS, Italy) and Polar Team System PRO 2 heart-rate sensor (Polar Electro, Finland) to recorder maximal heart rate. After 12 weeks of training (in season), the same players repeat an IR2 test to check performance improvements and verify whether the training programme is correct. The first element was to determine whether the improvement in distance covered during a test is better, the same, or worse with respect to the pre-season. After 12 weeks of training, the difference between the first trial (pre-season) and the second one (in-season) is statistically significant (ES: 0.48; p<0.05; 24%). At the same time, there has been a significant improvement in match physical performance. Regarding the importance of speed endurance training during a season, it is necessary to improve performance in IR2 test after 12 weeks and improve maximal oxygen uptake and glycolytic enzyme activity. Comparing match performance before (T1) the second trial IR2 with match performance after second (T2) trial of this test, there are statistically meaningful changes.